Sterility Testing and Contamination Analysis of the 99mTc Eluates from RIPDTEC Mo-99/Tc-99m Chromatographic Column Generator - Mouna, Syedzadi Mahbuba Monzur; Tanim, Md Tauhidul Islam; Rahman, Md Mustafizur; Hossain, Mohammed Anwar; Waheed, Momtaz Fatima; Akhter, Rabeya; Jahura, Fatema Tuj; Reza, Md Sultanur; Amin, Ruhul (Bangladesh Journal of Nuclear Medicine, 2025)
Metastable Technetium-99 is a widely used radioisotope in nuclear medicine that is administered to patients intravenously for imaging, functional studies of cells, and diagnosis of tumor cells of different body organs. Tc-99m is instantly available from the Mo-99/Tc-99m generator, accounts for more than 80% of all nuclear medicine procedures used for imaging, and is in growing demand worldwide every year. Hence, bulk manufacturing of this generator is carried out under strict aseptic conditions to ensure the sterility of Tc-99m. However, at the production stages of Tc-99m, there is still the possibility of getting contaminated with microbes and their endotoxin, which has a pyrogenic effect. The objective of this study is to assess and analyze the microbial and endotoxin contamination of the 3634 Tc-99m eluate samples collected from RIPDTEC Mo-99/Tc-99m chromatographic column generators. In the case of sterility testing, only 2 samples out of 3634 (0.05% of the total samples) exhibited bacterial growth after 14-day incubation in the media used to detect aerobic bacteria. In contrast, no fungal and anaerobic bacterial growth was observed during the 14-day incubation. In this study, 9 samples out of 3634 (0.25% of the total samples) showed gel clot formation in Tachypleus Amebocytes Lysate (TAL) kits used to detect endotoxin, which indicated the presence of endotoxin in those samples, and the amount was found 0.25-0.50 EU/ml. However, abnormal temperature rise was not observed in the case of any mice injected with eluate samples. Bangladesh J. Nuclear Med. 28(1): 109-113, 2025